Plan de marketing y ventas para la empresa "Artesanías Softy" - Chancosi, José F. (2020)
In the investigation it could be that it didn't have a Plan of Marketing the company Crafts Softy for the support and through the visits it was analyzed with the lack of a mission and vision, as well as political and objectives that there is the best address. A presage of sales is given this way in the course of the years; in the second chapter like equally it is analyzed the FODA he/she is carried out from the company to which has been carried out a crossing of the same one for their respective improvement in the points in which it is needed to optimize in a better way.